2006
DOI: 10.1002/ijc.22049
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the human/mouse syntenic common fragile site FRA7K/Fra12C1—Relation of FRA7K and other human common fragile sites on chromosome 7 to evolutionary breakpoints

Abstract: Common fragile sites (CFSs) are expressed as chromosome gaps in cells of different species including human and mouse as a result of the inhibition of DNA replication. They may serve as hot spots for DNA breakage in processes such as tumorigenesis and chromosome evolution. Using multicolor fluorescence in situ hybridization mapping, the authors describe here human CFS FRA7K on chromosome band 7q31.1 and its murine homolog Fra12C1. Within the syntenic FRA7K/Fra12C1 region lies the IMMP2L/Immp2l gene with a size … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 43 publications
2
33
0
Order By: Relevance
“…3). Additionally, 52 identified and in parts mapped FS were already published, but not included in the current genome browser versions (13,14,15,16,17,19,23,34). Most of these sites were confirmed in this study which underlines their eligibility to be appreciated as FS.…”
Section: ------------------------------------------------------------supporting
confidence: 50%
See 1 more Smart Citation
“…3). Additionally, 52 identified and in parts mapped FS were already published, but not included in the current genome browser versions (13,14,15,16,17,19,23,34). Most of these sites were confirmed in this study which underlines their eligibility to be appreciated as FS.…”
Section: ------------------------------------------------------------supporting
confidence: 50%
“…Additionally, differences in the observable FS-frequency within different individuals are well known (11,12). Besides these 88 official, database-annotated common FS others were observed and reported, including six recently reported new sites, particularly FRA4F (13), FRA7K (14), FRA6H (15), FRA9G (16), FRA13E (15) and FRA18C (17).…”
Section: Introductionmentioning
confidence: 94%
“…It appears, though, that they are densely packed in areas of high flexibility (Toledo et al, 2000). Notably, in a very recent study focusing on FS on chromosome 7, similar findings with regard to DNA-helix flexibility were drawn (Helmrich et al, 2007).…”
Section: Discussionmentioning
confidence: 60%
“…It appears that some CFSs contain flexibility peaks (Mishmar et al, 1998(Mishmar et al, , 1999Mimori et al, 1999;Zlotorynski et al, 2003), adenine-thymine runs (Zlotorynski et al, 2003) or an increased percentage of repetitive DNA (Morelli et al, 2002). Despite the usefulness of these sporadic observations, which generally concern the subset of the molecularly defined CFSs (Helmrich et al, 2007), a broad survey of the sequence characteristics of CFSs is missing.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, 2 integration sites were located in the mouse common fragile sites, Fra6B3 and Fra12C1 (17). Previous studies have revealed that common fragile sites are extremely unstable in the process of carcinogenesis and are always destroyed and rearranged in many tumor cells (18,19). Researchers have noted that most miRNAs play significant roles in tumorigenesis and metastasis (20).…”
Section: B Amentioning
confidence: 99%